ANALISA KINERJA PAPR PADA SISTEM OWDM MENGGUNAKAN WAVELET PACKET - Irwan Dinata (Jurnal Ecotipe (Electronic, Control, Telecommunication, Information, and Power Engineering), 2014)
In wireless communications, demand to provide high-speed data services with good performance raises new techniques to increase spectrum efficiency and improved signal quality due to frequency selective fading. OFDM is a multi-carrier technique can be used to accommodate all these requirements. But in its development, this OFDM still has some weaknesses such us still large PAPR values and lack of power spectral efficiency improvements, OWDM used to overcome these deficiencies. In OWDM, inverse wavelet packet transform (IWPT) is used to generate the transmitted symbol on the transmitter and the forward wavelet packet transform (WPT) will restore the transmitted data symbol on the receiver. The OWDM system will divide the frequency band into several sub-bands that independent and isolated spectral called subchannelization. From the test simulation obtained OWDM give some things that can be compared with OFDM. In PAPR reduction, OWDM lead in reducing the PAPR. In OWDM case, the smallest PAPR value is produced in small-order wavelet, Coiflet, use few sub-bands and QPSK modulation.